Muhyiddin İbnü'l-Arabi'de Arş tasavvuru ve istiva meselesi - Akkaya, Veysel (Serdar Yavuz, 2015)
Arş ve Hakk’ın ona istivâ etmesi, teşbih ve tecsimi çağrıştırması sebebiyle ulemânın izahında zorlandığı meselelerden biri olmuştur. Hatta İslam’ın ilk dönemlerinden itibaren konu ile ilgili kitaplar kaleme alınarak, mesele açıklanmaya çalışılmıştır. Selef âlimleri arşın “taht” manasına geldiğini söyleyerek, âyet ve hadislerdeki ifâdeleri yorumlamazken, sonraki dönemlerde yorumlar yapılmış ve arş ile anlatılmak istenenin “mülk” olduğu belirtilmiştir. Sonraki dönemlerde Sünnî kelamcıların çoğu, her iki manayı kapsadığı kanaatine varmışlardır. Muhyiddîn İbnü’lArabî de her iki mananın, bir diğerini tamamladığı görüşünü benimseyenlerdendir. O arş ve istivâ ile ilgili âyet ve hadisleri, tehzîh çerçevesinde yorumlamakla birlikte, teşbih kısmını tamamen yok saymak yerine, teşbih içeren ifadeleri, âyet ve hadislerde kullanıldığı ölçüde ve tehzîhe yakın bir şekilde anlamak gerektiği kanaatindedir. Ayrıca arş kavramına farklı anlamlar yükleyerek, çok yönlü ve zengin bir arş tasavvuru ortaya koymuştur. Arşı feleklerden biri kabul eden İbnü’l-Arabî, bu konuda İslam filozofları ile aynı fikri paylaşıyor gözükse de, onun felekten kastı aynı olmayıp, sembolik bir anlam ifade eder. Ona göre arş feleği, filozofların zannettiği gibi görülebilir âleme ait olmadığı için, ancak manevi keşifle bilinebilir. Arş, aynı zamanda varlık mertebelerinden biridir. Cisimler âleminde bütün cisimleri kuşatan en büyük ve ilk cisimdir. Bu cismin bir de ruhu vardır. Arşın cismi taht manasını anlamamızı sağlarken, ruhu da mülk manasını anlamamızı kolaylaştırır. Ona göre Hakk’ın arşa istivâsı, bir padişahın tahta oturması gibi anlaşılamaz. Bu istivâ Hakk’ın yüceliğini ortaya çıkarmasıdır. Arş âlemde ilâhî yönetimin merkezidir. Arşın insandaki tekâbülü, taht manasında kalbe karşılık gelirken, mülk manasında bedene karşılık gelir.

The nature of Throne (Arsh) and sitting of God upon it (istiwâ) has been one of the crucial matters discussed between scholars. Because sitting upon of God connotes anthropomorphism. From the very beginning of Islam up to these days it has been a controversial issue. The first period scholars said that the “arsh” means “throne”, but they abstained from interpreting the the Qur’anic verses and Prophetical Sayings (Hadith) which denote to this term. In later interpretations the term Arsh was interpreted as “sovereignty” (mulk). In short, most of Sunni theologians has been convinced that it covers both meanings. Ibn Arabi also is among the scholars who are in the opinion that both meanings complete one another. He, on one hand tried to interpret the Qur’anic verses and prophetical sayings related to Throne and sitting of God upon it from a perspective which insists on the unresembelance of God, and also tried to understand and interpret the anthropomorphic verses in accordance with the unresemblance of God without ignoring resemblance of Him. On the other hand he ascribed different meanings to the concept of ‘Throne’ and put forward a rich or multi-dimensional envision of Throne. Although he accepts the Throne as one of the spheres and appears as if he shares the same opinion with the Medieval Islamic philosophers, he also attributes some symbolical meanings to “the Throne.” He believes that the sphere of Throne can be known only by inspiration or by heart. According to him, the sphere of Arsh is not in the visible realm as understood by the philosophers, so it can be seen only by spiritual exploration. It is at the same time one of the levels of existence. It is the biggest entity that surrounds all other visible entities, and it has a soul. While its body gives us the meaning of ‘Throne,” its soul implies “sovereignty.” According to Ibn Arabi, it is wrong to understand “sitting of God upon the Throne” just like the sitting of a king on his throne. “Sitting upon” here implies to the glory or loftiness of God. Throne is the center of Divine management in the world. While the throne meaning of “Arsh” corresponds to the heart in human being, the sovereignty meaning of it corresponds to his bodily forces.
Muhyiddin İbnü'l Arabi'de Arş tasavvuru ve istiva meselesi
IBN ARABI’S ENVISION OF THE THRONE AND THE PROBLEM OF SITTING OF GOD UPON THE THRONE
Yrd. Doç. Dr. Veysel AKKAYA -- Sabahattin Zaim Üniversitesi İslami İlimler Fakültesi Tasavvuf Anabilim Dalı.
Keywords: Arş; İstivâ; Taht; Mülk; Tenzîh; Sitting upon; Throne; Management; Glory